The book of greens : a cook's compendium of 40 varieties, from arugula to watercress, with more than 175 recipes - Louis, Jenn; Squires, Kathleen (Ten Speed Press, 2017)
Presents recipes that use such greens as spinach, kale, and chard, including Swiss chard polenta and asparagus and spinach hummus.